Geo-Temporal Interpretation of Archival Collections with Neatline. - Nowviskie, Bethany; McClure, David; Graham, Wayne; Soroka, Adam; Boggs, Jeremy; Rochester, Eric (Literary & Linguistic Computing, 2013)
This article provides a brief description of Neatline, an open-source, Web-based suite of software produced by the Scholars' Lab at the University of Virginia Library. Neatline allows scholars and curators to interpret digitized cultural heritage collections with special attention to their temporal and geospatial dimensions. Here we describe the theoretical goals of Neatline, pragmatic decisions made during development of the toolset, and its primary features and affordances.